Development of Android Application-Based Game Media in Learning About Cells for 2nd Grade High School Students - Safitri, Annisa; Nikmah, Zumrotun (Proceeding International Conference on Religion, Science and Education, 2025)
In this digital era, innovation is needed in the field of education, especially as a learning media. This research aims to develop game media based on Android applications for learning about cell for 2nd-grade high school students. The development of this game media is based on the ADDIE model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The game media was designed with Construct 2 and Canva applications to be interactive and effective in helping students understand the concept of cell biology. The effectiveness of the game media was evaluated through a trial involving 2nd-grade high school students. The evaluation results show that this game media can help students understand the concept of cell biology as evidenced by the average score of students reaching 83.76.